Carotenoids from the soft coral Sarcophyton elegans - Minh, Chau Van; Kiem, Phan Van; Nam, Nguyen Hoai; Cuong, Nguyen Xuan; Thao, Nguyen Phuong; Dang, Nguyen Hai; Quang, Tran Hong; Dat, Nguyen Tien; Thung, Do Cong; Thuy, Dinh Thi Thu (Vietnam Journal of Chemistry, 2012)
By various chromatographic separations, three carotenoids were isolated from the soft coral Sarcophyton elegans. They were elucidated as peridinin (1), peridininol (2), and all-trans-peridininol-5,8-furanoxide (3) by spectroscopic methods and in comparison with reported data. This is the first report of 3 from soft corals.